A modified minimally invasive surgery for thoracic pyogenic spondylitis: Percutaneous pedicle screw fixation in combination with a vertebral debridement in a separate posterolateral approach—A case report. Issue 12 (5th December 2022) - Sato, Yuki; Hashimoto, Ko; Matsuda, Michiharu; Onoki, Takahiro; Kamimura, Masayuki; Takahashi, Kohei; Onoda, Yoshito; Chiba, Daisuke; Mori, Yu; Kanno, Haruo; Yamamoto, Nobuyuki; Aizawa, Toshimi
Abstract: In this report, we present a successfully treated case of intractable thoracic pyogenic spondylitis using one‐step curettage/bone grafting of spinal anterior segment and less‐contaminated percutaneous spinal posterior fixation via separated posterior approaches, which was not compatible with conventional spinal instruments. Abstract : The percutaneous pedicle screws (PPS) were inserted from T8–10 to L1–3 (A, B). The skin incisions for PPS installation were placed medial to the common insertion point to avoid violating the posterolateral approach for curettage. Each PPS was inserted perpendicularly to the body surface (C, D).